QUESTION ANSWER RELATIONSHIP (QAR) STRATEGY IN CRITICAL READING ON NARRATIVE TEXT - Wila Suswika; Rina Herlina; Didih Faridah (Universitas Galuh, 2020)
This study figured out the way a teacher implement of QAR strategy in critical reading on narrative text, and investigate students overcome the difficulties in answering narrative text questions by using QAR strategy in critical reading. This study used a case study as a research design. The participant was an English teacher and twenty students of tenth grade in one of senior high school in Tasikmalaya, Indonesia. Several instruments were used to collect the data. The first was classroom observation, it was analyzed by transcribing and drawing the conclusion. The second was an interview with the English teacher, it was analyzed by describing the teacher answer, and the last was students' reflective journal that was analyzed by describing students’ opinions. The result showed that the QAR strategy was helpful for students not only to answer the questions but also to understand the text and can help them in critical reading when answering the narrative text questions. Most of the students argued that to overcome the difficulties in answering narrative text questions by using the QAR strategy, students have to understand the whole text with correctly, they can associate the text with their background knowledge and experiences in their lives.Keywords: Question-Answer Relationship (QAR) Strategy, Critical Reading, Narrative